The Satisfaction with Daily Occupations (SDO-13) Scale: Psychometric Properties among Clients in Primary Care in Sweden. Issue 1 (2nd January 2016) - Wästberg, Birgitta A.; Persson, Elisabeth B.; Eklund, Mona
ABSTRACT: This article describes the results to expand and develop the use of the Satisfaction with Daily Occupations (SDO-13) Scale. Data were collected in primary care before (I) and after intervention (II) among clients with stress-related disorders and musculoskeletal pain. The Cronbach's alpha values of the SDO-13 Scale were 0.80 and 0.88. Convergent validity was assessed against global occupational satisfaction and general health, resulting in r s = –0.65 ( p < 0.001) and r s = –0.46 ( p < 0.001). The SDO-13 Scale could not discriminate between the primary care sample and a psychiatric sample ( p = 0.15), whereas number of current occupations could ( p < 0.001). The SDO-13 was not sensitive to change ( p = 0.92). Future studies need to explore criterion and construct validity based on more dissimilar samples and more standardized interventions. Applications of these results to practice are discussed.